Avaliação do comportamento alimentar e comportamento de grazing em pessoas com diabetes mellitus tipo 2 atendidas em um hospital público de referência em Belém, Pará - GOMES, Ana Paula Alvarenga Seguins (2024)
Type 2 Diabetes Mellitus (T2DM) is a disease defined by chronic hyperglycemia. Nutritional treatment should be individualized, according to each patient and respecting their characteristics and preferences. Grazing, characterized by eating small amounts of food repetitively, in conjunction with other dysfunctional eating behaviors, can impact the therapy and control of T2DM. In this sense, the objective of this study is to evaluate the characteristics of eating behavior and grazing behavior in people with DM2 treated at a public hospital in Belém-PA. This is a cross-sectional, descriptive and analytical study conducted with patients with DM2, aged between 20 and 64 years, followed at the endocrinology outpatient clinic of a public hospital in Belém-PA. Socioeconomic, demographic, clinical, and anthropometric data (weight and height) were collected to calculate the body mass index (BMI). The Three Factor Eating Questionnaire (TFEQ-R21) was applied to assess eating patterns, and the Repetitive eating questionnaire (REP-EAT_Q) was applied to assess grazing behavior patterns. The study was approved by the Research Ethics Committee (opinion number 6.087.34). For statistical analysis, the Statistical Package for Social Science, version 21, was used, considering a statistical significance level of p<0.05. A total of 44 participants were evaluated, 72.2% of whom were female and with a mean age of 55.41±6.41. Most were classified as overweight (43.2%). Regarding eating behavior, a higher mean of cognitive restriction was observed (49.12±23.17). In relation to grazing, the answers indicating repetitive eating had an average of (1.47±1.28) and those of compulsive grazing had a mean of (1.14±0.89). Regarding correlations, it was observed that uncontrolled eating was correlated with repetitive eating (r²=0.544; p=0.000) and compulsive grazing (r²=0.521; p=0.000), as well as emotional eating was correlated with repetitive eating. Knowledge and identification of eating behavior patterns and grazing behavior are of great importance for early intervention in the follow-up of people with DM2, which should be supported by the multidisciplinary team, aiming at complete care and more assertive treatment of patients.